"So delightful a temporary home": The Material Culture of Domesticity in Late Nineteenth-century English Convalescent Institutions. (18th June 2021) - Anders, Eli Osterweil
Abstract: This article examines the material culture of domesticity in late nineteenth-century English convalescent institutions. Convalescent homes drew on powerful Victorian ideas about the physical and moral benefits of "home-like" domestic comfort, which they contrasted with the "institutional" environment of hospitals and the degrading surroundings of urban slums. Administrative records, press accounts, photographs, and patient letters reveal how convalescent homes cultivated temporary home-like environments through architecture, interior decoration, and behavioral expectations and routines. Convalescent homes drew on heterogeneous models of domesticity, including the grand architecture of country estates, the possession-packed spaces of middle-class homes, and the recreational spaces of male social clubs. Nevertheless, they shared a belief in the power of domestic spaces, comforts, and practices to support the recovery of convalescents and to influence their identity and behavior. The material culture and practices of domesticity deployed in convalescent homes encouraged reflection, self-improvement, and self-control—qualities essential to the cultivation of respectable, self-governing, liberal citizens. Nevertheless, the meanings and experiences of these spaces were also shaped by inmates, whose expectations and experiences did not always align with the ideal image of home that authorities wished to create.